Wnt11 preserves mitochondrial membrane potential and protects cardiomyocytes against hypoxia through paracrine signaling. Issue 2 (28th August 2019) - Li, Hong‐Xia; Lin, Jia; Jiang, Bin; Yang, Xiang‐Jun
Abstract: We investigated the effect of Wnt11 on mitochondrial membrane integrity in cardiomyocytes (CMs) and the underlying mechanism of Wnt11‐mediated CM protection against hypoxic injury. A rat mesenchymal stem cell (MSC) line that overexpresses Wnt11 (MSC Wnt11 ) and a control cell line transduced with empty vector (MSC Null ) were established to determine the cardioprotective role of Wnt11 in response to hypoxia. Mitochondrial membrane integrity in MSC Wnt11 cells was assessed using fluorescence assays. The role of paracrine signaling mediated by vascular endothelial growth factor (VEGF), basic fibroblast growth factor (b‐FGF), and insulin‐like growth factor 1 (IGF‐1) in protecting CMs against hypoxia were investigated using cocultures of primary CMs from neonatal rats with conditioned medium (CdM) from MSC Wnt11 . MSC Wnt11 cells exposed to hypoxia reduced lactate dehydrogenase release from CMs and increased CM survival under hypoxia. In addition, CMs cocultured with CdM that were exposed to hypoxia showed reduced CM apoptosis and necrosis. There was significantly higher VEGF and IGF‐1 release in the MSC Wnt11 group compared with the MSC Null group, and the addition of anti‐VEGF and anti‐IGF‐1 antibodies inhibited secretion. Moreover, mitochondrial membrane integrity was maintained in the MSC Wnt11 cell line. In conclusion, overexpression of Wnt11 in MSCs promotes IGF‐1 and VEGF release, thereby protecting CMs against hypoxia. Abstract : Although Wnt11 is known to protect cardiomyocytes (CMs) against hypoxia, its effect on mitochondrial membrane integrity and mechanism of cardioprotection are unclear. By genetically engineering mesenchymal stem cells to overexpress Wnt11, we showed that mitochondrial membrane integrity was maintained in CMs with upregulated Wnt11. In addition, our study revealed that CM protection against hypoxic stress is mediated through the paracrine factors IGF‐1 and vascular endothelial growth factor.